1978
DOI: 10.1042/bj1740231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestrogen and 1,25-dihydroxycholecalciferol on 25-hydroxycholecalciferol metabolism in primary chick kidney-cell cultures

Abstract: Primary cultures of chick kidney cells convert 25-hydroxycholecalciferol into more-polar metabolites. Cells from vitamin D-deficient chicks have high 25-hydroxycholecalciferol 1 alpha-hydroxylase (1 alpha-hydroxylase) activity, but no 25-hydroxycholecalciferol 24-hydroxylase (24-hydroxylase) activity. Physiological concentrations of 1,25-dihydroxycholeclaciferol suppress 1 alpha-hydroxylase and induce 24-hydroxylase activity. The inhibition of 1 alpha-hydroxylase preceded the induction of 24-hydroxylase. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Perhaps the extracellular calcium concentration had little influence on the intracellular calcium concentration in these experiments. However, a number of studies have reported that PTH stimulates 1,25(OH)2D3 production by intact renal cells in vitro (30,31,(33)(34)(35)(36)(37). Stimulation ofthe renal la-hydroxylase in these reports required 2-200 ng/ml PTH, the same concentration range that increased the amount of 1,25(OH)2D3 in keratinocytes incubated with 250HD3.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the extracellular calcium concentration had little influence on the intracellular calcium concentration in these experiments. However, a number of studies have reported that PTH stimulates 1,25(OH)2D3 production by intact renal cells in vitro (30,31,(33)(34)(35)(36)(37). Stimulation ofthe renal la-hydroxylase in these reports required 2-200 ng/ml PTH, the same concentration range that increased the amount of 1,25(OH)2D3 in keratinocytes incubated with 250HD3.…”
Section: Resultsmentioning
confidence: 99%
“…Their free 1,25-(OH)2D3 concentration and their intestinal calcium absorption, however, both remained unchanged, indicating that the biological response of the target organ corresponds to the free rather than the total hormone concentration (36). If the increase in serum 1,25-(OH)2D3 is only secondary to the increase in serum DBP, it becomes clear why the stimulatory effect of estrogens on 1,25-(OH)2D3 production in vivo (37,38) cannot be observed in cultures of isolated kidney cells (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…The development of kidney cell cultures by our laboratory and by others (32)(33)(34)(35)(36) has for the first time offered a system for the investigation in vitro of long- (34,35), and steroid hormones (36) have been reported. In our system we have studied the properties of the hydroxylases in cultured cells and we have found that they were similar to those ofthe enzymes in fresh chick kidney preparations.…”
Section: Discussionmentioning
confidence: 99%